Assessment of stump invagination versus simple ligation in open appendicectomy - Khan, S (Journal of Institute of Medicine Nepal, 2010)
Introduction: Operation of appendix is very common abdominal surgery that is done by general surgeons. Some surgeon prefer to invaginate the appendix stump while others don’t. Aim of the study was to compare the technique of ligation and invagination of the appendix stump with simple ligation of the appendix stump during appendicectomy for acute appendicitis. Methods: A prospective comparative study of 150 appendicectomies were done in the Department of General Surgery, Nepalgunj medical college (NGMC),Nepalgunj,Nepal from June 2001-May 2007in unit III. All patients with uncomplicated and complicated acute appendicitis who underwent open appendicectomy and had appendicular stump for ligation and invagination or simple ligation, were divided into two groups. In group-I ligation with invagination and in group-II, simple ligation of appendix stump was carried out. Patients were followed up for 3-6 months to check the development of complications Results: Both groups were similar with respect to age and sex. Invagination of the stump after ligation of the stump was done in 70 patients while simple ligation was done in 80 cases. The incidence of postoperative pyrexia (18.57% and 22.5%), wound infection (27.15% and 30.0%) and postoperative paralytic ileus (25.71% and 27.5%) was in group-I and group-II respectively. Conclusions: Simple ligation of appendix stump is as safe a procedure as ligation and invagination of appendix stump during appendicectomy. DOI: http://dx.doi.org/10.3126/joim.v32i1.3994 Journal of Institute of Medicine, April, 2010; 32:1 pp.7-10